PENGARUH KEBIJAKAN BEBAS VISA KUNJUNGAN INDONESIA TERHADAP CHINA DALAM BIDANG KETENAGAKERJAAN PADA TAHUN 2015-2018 - M. Rafid Rizqullah; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study examines the effect of the implementation of Indonesia's visa-free visit policy on China in the field of employment. The expansion of the list of countries receiving visa-free facilities from the previous policy shows success with the increase in the number of foreign tourists to Indonesia and is also followed by an increase in the country's foreign exchange earnings. But behind all these positive results, the visa-free policy has a negative impact that threatens the sovereignty of the Indonesian state. This study uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, and websites. This study uses the perspective of Realism and Foreign Policy theory. The results of this paper show that behind the positive results resulting from the application of the visa-free policy, there is a negative impact, namely the entry of illegal Chinese foreign workers. The expansion of the visa-free policy is a gap for the Indonesian government amid the influx of foreign workers from China. The visa-free visit policy which was originally intended to attract foreign tourists was used by illegal Chinese foreign workers to be able to enter and work in Indonesia. They enter with the mode of pretending to be tourists using visa-free facilities without going through legal or applicable requirements and administrative processes. Keywords: Visa Free, Foreign Workers, Illegal.